Review of Ongoing Activities and Challenges to Improve the Care of Patients With Type 2 Diabetes Across Africa and the Implications for the Future - Godman, Brian; Basu, Debashis; Pillay, Yogan; Mwita, Julius C.; Rwegerera, Godfrey Mutashambara; Anand Paramadhas, Bene D.; Tiroyakgosi, Celda; Okwen, Patrick Mbah; Niba, Loveline Lum; Nonvignon, Justice; Sefah, Israel; Oluka, Margaret; et al. (Frontiers in Pharmacology, 2020)
Background There has been an appreciable increase in the number of people in Africa with metabolic syndrome and Type 2 diabetes (T2DM) in recent years as a result of a number of factors. Factors include lifestyle changes, urbanisation, and the growing consumption of processed foods coupled with increasing levels of obesity. Currently there are 19 million adults in Africa with diabetes, mainly T2DM (95%), estimated to grow to 47 million people by 2045 unless controlled. This has a considerable impact on morbidity, mortality and costs in the region. There are a number of issues to address to reduce the impact of T2DM including improving detection rates and current access to services alongside addressing issues of adherence to prescribed medicines. There are also high rates of co-morbidities with infectious diseases such as HIV and tuberculosis in patients in Africa with T2DM that require attention. Objective Document ongoing activities across Africa to improve the care of patients with T2DM especially around issues of identification, access, and adherence to changing lifestyles and prescribed medicines. In addition, discussing potential ways forward to improve the care of patients with T2DM based on ongoing activities and experiences including addressing key issues associated with co-morbidities with infectious diseases. Our Approach Contextualise the findings from a wide range of publications including internet based publications of national approaches coupled with input from senior level government, academic and other professionals from across Africa to provide future guidance. Ongoing Activities A number of African countries are actively instigating programmes to improve the care of patients with T2DM starting with improved diagnosis. This recognises the growing burden of non-communicable diseases across Africa, which has been neglected in the past. Planned activities include programmes to improve detection rates and address key issues with diet and lifestyle changes, alongside improving monitoring of care and activities to enhance adherence to prescribed medicines. In addition, addressing potential complexities involving diabetes patients with infectious disease co-morbidities. It is too early to fully assess the impact of such activities, Conclusion There are a number of ongoing activities across Africa to improve the management of patients with diabetes including co-morbidities. However, more needs to be done considering the high and growing burden of T2DM in Africa. Ongoing research will help further benefit resource allocation and subsequent care.